The Impact of Digital Competence, Compensation, and Transformational Leadership on Career Development of Lecturers - Afdalisma Afdalisma; Chabullah Wibisono; Bambang Satriawan (Goodwood, 2025)
Purpose: This study aimed to analyze the effect of digital competence, compensation, and transformational leadership on lecturer career development, with achievement motivation as an intervening variable and organizational support as a moderating variable at Private Universities (PTS) in West Sumatra. Research methodology: This study uses a quantitative approach with SEM-PLS analysis on 293 lecturers selected through random sampling, complemented by qualitative data from 20 purposively selected informants, including lecturers and university stakeholders. Results: Digital competence, compensation, and transformational leadership positively influenced achievement motivation and lecturer career development. Achievement motivation acts as a significant intervening variable, whereas organizational support strengthens its effect on career development. Conclusions: The study concluded that improving digital competence, providing adequate compensation, and implementing transformational leadership are essential factors in enhancing lecturers’ achievement motivation and career development. Organizational support further strengthens this relationship. Limitations: This study is limited to private universities in West Sumatra, which may restrict the generalizability of the findings to other regions or types of higher-education institutions. Additionally, the use of cross-sectional data limits our ability to capture long-term effects. Contributions: This study contributes to the theoretical development of competency- and motivation-based academic-career models. Practically, it provides insights for higher-education institutions to formulate strategic policies that support sustainable lecturer development and improve the overall quality of higher education, particularly in private universities.